Medicare expenditures for elderly patients undergoing surgical clipping or endovascular intervention for unruptured cerebral aneurysms. (24th March 2016) - Bekelis, Kimon; Gottlieb, Dan; Su, Yin; Labropoulos, Nicos; Bovis, George; Lawton, Michael T; MacKenzie, Todd A
Abstract : Background: The cost difference between the two treatment options (surgical clipping and endovascular therapy) for unruptured cerebral aneurysms remains an issue of debate. We investigated the association between treatment method for unruptured cerebral aneurysms and Medicare expenditures in elderly patients. Methods: We performed a cohort study of 100% Medicare fee-for-service claims data for elderly patients who underwent treatment for unruptured cerebral aneurysms from 2007 to 2012. In order to control for measured confounding we used multivariable regression analysis with mixed effects to account for clustering at the Hospital Referral Region (HRR) level. An instrumental variable (regional rates of endovascular treatment) analysis was used to control for unmeasured confounding by creating pseudo-randomization on the treatment method. Results: During the study period 8705 patients underwent treatment for unruptured cerebral aneurysms and met the inclusion criteria. Of these, 2585 (29.7%) had surgical clipping and 6120 (70.3%) had endovascular treatment. The median total Medicare expenditures in the first year after the admission for the procedure were $46 800 (IQR $31 000–$74 400) for surgical clipping and $48 100 (IQR $34 500–$73 900) for endovascular therapy. When we adjusted for unmeasured confounders, using an instrumental variable analysis, clipping was associated with increased 7-day Medicare expenditures by $3527 (95% CI $972 to $5736) and increased 1-year Medicare expenditures by $15 984 (95% CI $9017 to $22 951). Conclusions: In a cohort of Medicare patients, after controlling for unmeasured confounding, we demonstrated that surgical clipping of unruptured cerebral aneurysms was associated with increased 1-year expenditures compared with endovascular treatment.